A Study on the Effectiveness of I-Sparx for Nunavut Youth: Can an E-Intervention Mental Health Tool in the Form of a Computer Game Improve Emotion Regulation? - Barnhardt, Jenna (2023)
This study examines how the e-intervention computer game, I-SPARX, may affect user emotion regulation. I-SPARX was designed for at-risk ᐃᓄᐃᑦ(Inuit) youth to teach cognitive behavioural skills and assist with improving mental health and emotional well-being. Data were collected from 112 ᐃᓄᐃᑦ (Inuit) youth participants from 25 communities in Nunavut who played I-SPARX and completed pre- and post-game outcome measures. Mixed model analysis was conducted at two time points to examine changes before and after playing the game in 6 domains meant to assess learning objectives and skills development: finding hope, being active, dealing with emotions, overcoming problems, recognizing challenging and unhelpful thoughts, and overall wellness. Results showed positive shifts in participant responses across all categories including emotion regulation skill development. This preliminary data is promising, suggesting that I-SPARX could help teach ᐃᓄᐃᑦ(Inuit) youth skills to manage emotions when they are confronted with challenging situations where negative and unhelpful thoughts arise.